Thermoelectric properties of silicon oxide - Olimov Lutfiddin; Khojimatov Islombek (E3S Web of Conferences, 2023)
The article describes the results obtained from the study of the thermal conductivity of granulated silicon particles covered with a layer of silicon oxide. The results of the study show that the thermal conductivity of granulated silicon increases from λ ~1,12 W/mK to λ ~2,74 W/mK at T~300÷600 K, which is consistent with the results of silicon oxide (λSiO2~1 W/mK). It was also observed that the electrical conductivity changes in the range of σ~0,0038÷0,017 (Ohm·sm)-1. The results of the study were explained based on the formation of a layer of silicon oxide on the surface of granulated silicon particles obtained by powder technology. Temperature-induced thermal voltaic effects are observed in the silicon oxide layer. This process depends on the formation of electron-hole pairs in cases with localized access, which leads to an increase in parameters λ and σ.